Unveiling the Linguistic Landscape of Educational Spaces in a Remote Indonesian Area - Fransiskus Dinang Raja; Maria Wisendy Sina; Renol Aprico Siregar (Universitas Sanata Dharma, 2025)
The signs materialized in the linguistic landscape (LL) symbolize what people believe about the language. Hence, most studies of LL focus on both language use and language ideology. While the study of LL is quite general worldwide, it is relatively new in East Nusa Tenggara, especially for those investigating LL in the educational setting. This study aimed to 1) find what language patterns and languages are exposed in the LL of the educational setting in Maumere City, NTT province, and 2) find the language ideology as the basis of why certain language was used and other language was rarely used. This research employed a qualitative case study. Data were obtained through documentation and interviews with 9 informants from 8 high schools and 1 university. The data were analyzed in three steps of qualitative data analysis: data condensation, data display, and conclusion drawing. The results indicated that there were three sign patterns, namely, monolingual, bilingual, and multilingual signs. There were 7 languages used in the three sign patterns above, namely Indonesian, English, Indigenous languages, Sanskrit, Japanese, German, and Latin. The situation represented through the school and university landscape manifested the language ideology. Interviews with informants revealed four main themes: language policy influencing language practice, language as a learning tool, language as a school identity marker, and language as a symbol of culture. These results are expected to provide a wider insight into the LL study in Indonesia.